Spherical manganese cobaltate loaded nickel-molybdenum nanosheet and preparation method and application thereof

By growing NiMo-LDH nanosheets in situ on the surface of MnCo2O4 material to form a core-shell structure, the problems of insufficient charge storage capacity caused by the small specific surface area of ​​MnCo2O4 material and the stability reduction caused by the change in the volume of metal sulfide are solved, and high specific capacitance and good cycling stability are achieved.

CN119673677APending Publication Date: 2025-03-21GUILIN UNIV OF ELECTRONIC TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411963915.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, the specific surface area of ​​MnCo2O4 material is small, resulting in insufficient charge storage capacity. At the same time, metal sulfides as core-shell structures have problems with reduced stability caused by volume changes.

Method used

The spinel-structured oxide MnCo2O4 is used as the substrate material. By growing NiMo-LDH nanosheets in situ on its surface, a core-shell structure is formed, the micromorphology of LDH is adjusted, volume changes are prevented, and stability is improved.

Benefits of technology

The specific capacitance and cyclic stability of the material are improved, ensuring that the capacitance retention rate reaches 70-80% at high cycle times, while maintaining the stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673677A_ABST
    Figure CN119673677A_ABST
Patent Text Reader

Abstract

The invention discloses a spherical manganese cobalt oxide loaded nickel molybdenum nanosheet MnCo2O4 / NiMo-LDH, which is prepared by the following steps: preparing a spherical Mn-Co-gly precursor by a hydrothermal method, calcining to obtain spherical manganese cobalt oxide MnCo2O4, and loading layered hydroxide NiMo-LDH by a hydrothermal method by taking MnCo2O4 as a carrier, thereby obtaining the spherical manganese cobalt oxide loaded nickel molybdenum nanosheet MnCo2O4 / NiMo-LDH. The microstructure of the MCO / NiMo-LDH is of a spherical structure, the surface of the MCO / NiMo-LDH is uniformly coated with a nanosheet layer, the size of the MCO / NiMo-LDH is 1.4-1.5 microns, and the NiMo-LDH serves as a carrier and is loaded on the surface of the MCO in situ; meanwhile, the MCO / NiMo-LDH has a core-shell structure, the MCO is the core structure, and the NiMo-LDH is the shell structure. The preparation method comprises the following steps: 1, preparing manganese cobaltate MCO; and 2, preparation of the MCO / NiMo-LDH. When the material is used as a supercapacitor electrode material, the specific capacitance is 900-1000F g <-1 >; and when the number of cycles is 5000, the capacitance retention rate is 70-80%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of supercapacitors, and in particular to a spherical manganese cobaltate loaded nickel-molybdenum nanosheet and a preparation method and application thereof. Background Art

[0002] Transition metal oxides have the characteristic of variable valence state, so they can promote electron transfer and thus have good electrochemical charge storage function. In addition, they have the ability of bulk ion embedding and pseudocapacitance near the surface, and can realize charge storage through Faraday charge storage on the surface of the material. Therefore, they have high theoretical specific capacitance and good reversibility, and can be used as supercapacitor materials.

[0003] Among them, single metal oxides, such as MnO2 or Co3O4, have the problem of little oxidation state change; in addition, precious metal oxides, such as RuO2, have the problem of high raw material cost. Among transition metal oxides, MnCo2O4 has a cubic spinel structure, which has good structural stability and can improve the electrochemical cycle stability during the electrochemical cycle. In addition, both manganese ions and cobalt ions in MnCo2O4 exist in multiple oxidation states, which can obtain higher energy density and power density. For example, prior art 1 (《Investigation on spinel MnCo2O4 electrode material prepared via controlled and uncontrolled synthesis route for supercapacitor application》DOI: 10.1007 / s10853-015-9132-8) synthesized MnCo2O4 by combustion and hydrothermal methods, and the energy density was 5mV s -1 The specific capacitance at the scan rate is 671 F g -1 , and the capacitance retention rate in 1000 continuous cycles is 92%. Due to the unique cubic spinel structure of MnCo2O4, the cations in the spinel structure can occupy two different lattice positions: tetrahedral positions and octahedral positions. This structural diversity enables the spinel structure to adapt to different chemical compositions, so that the technical solution obtains excellent cycle stability. However, the specific surface area of ​​MnCo2O4 obtained by this technical solution is small, resulting in a small contact area with the electrolyte, which ultimately leads to the problem of insufficient charge storage capacity.

[0004] In order to solve the problem of low specific capacitance caused by low specific surface area, MnCo2O4 can be compounded with other substances to form a core-shell structure. The shell structure increases the specific surface area and the reaction active sites, thereby improving the specific capacitance of the material. For example, prior art 2 (Hierarchical NiCo2O4@NiCo2S4 Nanocomposite on Ni Foam as an Electrode for Hybrid Supercapacitors DOI: 10.1021 / acsomega.8b00742) uses a hydrothermal method and calcination process to prepare NiCo2O4@NiCo2S4 with a core-shell structure. -1 The specific capacitance is 1872Fg-1, but the capacitance retention rate after 4000 charge and discharge cycles is only 65%. Although this technical solution improves the specific capacitance of the material, due to the sulfide under long cycle conditions, there is a phenomenon of unstable microstructure. The reason is that, in order to improve the specific capacitance performance, the technical solution uses sulfide as a core-shell structure according to common knowledge in the art, but such metal sulfides all have the problem of significant volume change during the cycle, which directly leads to the destruction of the microstructure and reduces the cycle performance, that is, using metal sulfide as the material component of the core-shell structure, there is a technical problem of reduced stability caused by volume change.

[0005] In order to solve the above problems, the material used as the carrier, in addition to having high electrochemical performance, also needs to have the characteristics of volume stability, that is, it needs to have the characteristics of controllable morphology, thereby solving the problems of electrochemical performance and stability of the composite material at the same time. For example, prior art 3 ("Dandelion-Like CuCo2O4@NiMn-LDH Core / Shell Nanoflowersfor Excellent Battery-Type Supercapacitor" DOI: 10.3390 / nano13040730) uses a two-step hydrothermal method to prepare CuCo2O4@NiMn-LDH core / shell nanoflowers (CCO NF). At 1Ag -1 The specific capacity is 2156.53F g at a current density of -1 In 5Ag -1 After 2500 cycles, the capacity is still maintained at 94.6%. The nanoflowers formed by NiMn-LDH have the characteristics of high specific surface area, and the core-shell structure can improve the stability of the overall material. However, the solution environment for preparing NiMn-LDH electrode materials in this technical solution is alkaline, which directly leads to the rapid precipitation of Mn-based hydroxides under alkaline conditions, resulting in structural aggregation and affecting the morphology of the final material. Summary of the invention

[0006] The purpose of the present invention is to provide a spherical manganese cobalt oxide loaded nickel molybdenum nanosheet and its preparation method and application. In order to solve the technical problems existing in the current technical solution, the following methods can be used to improve it:

[0007] The specific principles and methods involved include:

[0008] 1. Using spinel structure oxide MnCo2O4 as the base material, it has the characteristics of high structural stability;

[0009] 2. NiMo-LDH is grown in situ on the surface of MnCo2O4, and Mo in Mo-based hydroxide is used. 6+ It has the characteristics of high oxidation state, which can adjust the micromorphology of LDH to overcome the problem of rapid precipitation of Mn-based hydroxide under alkaline conditions, resulting in unstable micromorphology;

[0010] 3. A core-shell structure is formed by MnCo2O4 and NiMo-LDH, and the interaction at the interface is utilized to promote the uniform nucleation of NiMo-LDH on the surface of MnCo2O4, so that the nucleation and growth of LDH on the surface of the metal oxide reach a thermodynamic and kinetic balance, alleviate the volume change during the cycle, and improve stability.

[0011] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0012] A spherical manganese cobalt oxide loaded nickel-molybdenum nanosheet MnCo2O4 / NiMo-LDH, firstly preparing a spherical Mn-Co-gly precursor by a hydrothermal method, then calcining to obtain spherical manganese cobalt oxide MnCo2O4, then using MnCo2O4 as a carrier to load layered hydroxide NiMo-LDH by a hydrothermal method, to obtain spherical manganese cobalt oxide loaded nickel-molybdenum nanosheet MnCo2O4 / NiMo-LDH, referred to as MCO / NiMo-LDH;

[0013] The raw materials for preparing the Mn-Co-gly are manganese nitrate tetrahydrate, cobalt nitrate hexahydrate, isopropanol and glycerol;

[0014] The raw materials for preparing the NiMo-LDH are nickel nitrate hexahydrate, sodium molybdate dihydrate and urea;

[0015] The microscopic morphology of the MCO / NiMo-LDH is a spherical structure, the surface of which is uniformly coated with nanosheets with a size of 1.4-1.5 μm. NiMo-LDH is used as a carrier and is in situ loaded on the surface of MCO. At the same time, MCO / NiMo-LDH has a core-shell structure, in which MCO is a core structure and NiMo-LDH is a shell structure.

[0016] A method for preparing spherical manganese cobalt oxide loaded nickel-molybdenum nanosheets MnCo2O4 / NiMo-LDH comprises the following steps:

[0017] Step 1, preparation of manganese cobalt oxide MnCo2O4, first, under certain conditions, tetrahydrated manganese nitrate and hexahydrated cobalt nitrate are placed in isopropanol and stirred to obtain solution A, then, under certain conditions, glycerol is placed in solution A and continued to stir to obtain solution B, under certain conditions, solution B is subjected to hydrothermal reaction, then, the reaction product is washed with anhydrous ethanol, and then vacuum dried under certain conditions to obtain Mn-Co-gly precursor, and finally, under certain conditions, the Mn-Co-gly precursor is calcined to obtain spherical manganese cobalt oxide MnCo2O4, referred to as MCO;

[0018] In the step 1, the molar ratio of manganese nitrate tetrahydrate to cobalt nitrate hexahydrate is 1:2;

[0019] In step 1, the conditions for preparing solution A and solution B are that the stirring time is 30-60 min; the conditions for vacuum drying are that the drying temperature is 60-80° C. and the drying time is 12-24 h;

[0020] In the step 1, the conditions for the hydrothermal reaction of solution B are: the hydrothermal temperature is 120-140° C., and the hydrothermal time is 4-6 hours;

[0021] In the step 1, the calcination conditions are: under air conditions, the calcination temperature is 350-450° C., and the calcination time is 2-3 hours;

[0022] Step 2, preparation of MCO / NiMo-LDH, first, under certain conditions, nickel nitrate hexahydrate, sodium molybdate dihydrate and urea are placed in deionized water and stirred to obtain solution D, then, the MCO obtained in step 1 is placed in solution D to obtain solution E, then, under certain conditions, solution E is subjected to hydrothermal reaction, and finally, the reaction product is washed with deionized water and anhydrous ethanol in turn, and then vacuum dried under certain conditions to obtain spherical manganese cobalt oxide loaded nickel molybdenum nanosheets MnCo2O4 / NiMo-LDH, referred to as MCO / NiMo-LDH;

[0023] In the step 2, the molar ratio of nickel nitrate hexahydrate, sodium molybdate dihydrate and urea is 1:1:5, and the mass of MCO is 0.08-0.14 g;

[0024] In step 2, the conditions for preparing solution D and solution B are that the stirring time is 30-60 min; the conditions for vacuum drying are that the drying temperature is 60-80° C. and the drying time is 12-24 h;

[0025] In step 2, the conditions for the hydrothermal reaction of solution E are: the hydrothermal temperature is 120-140° C., and the hydrothermal reaction time is 4-6 hours; the conditions for vacuum drying are: 60-80° C., the drying temperature is 60-80° C., and the drying time is 12-24 hours.

[0026] Spherical manganese cobalt oxide loaded with nickel molybdenum nanosheets MCO / NiMo-LDH, when used as supercapacitor electrode materials, the specific capacitance of MCO / NiMo-LDH is 900-1000F g -1 ; With MCO / NiMo-LDH as the positive electrode and activated carbon AC as the negative electrode, the capacitance retention rate is 70-80% when the cycle number is 5000 times.

[0027] The present invention characterizes and tests the obtained MCO / NiMo-LDH composite material, and the results are as follows:

[0028] In order to prove the composition of MCO / NiMo-LDH, XRD test was carried out. The test results showed that MCO / NiMo-LDH had characteristic peaks of NiMo-LDH in addition to the characteristic peaks of MnCo2O4.

[0029] In order to prove the microstructure of MCO / NiMo-LDH, SEM test was carried out. The test results showed that the microstructure of MCO / NiMo-LDH was a spherical structure with a size of 1.4-1.5μm, and was evenly coated with a nanosheet structure. Combined with the XRD test results, it can be seen that the nanosheet structure is NiMo-LDH.

[0030] In order to further prove the microstructure of MCO / NiMo-LDH, TEM test was carried out. The test results showed that the microstructure of MCO / NiMo-LDH was a core-shell structure. Combined with the XRD test results, it can be seen that MCO is a core structure and NiMo-LDH is a shell structure.

[0031] In order to prove the electrochemical performance of MCO / NiMo-LDH, electrochemical performance tests were carried out. The test results showed that the charge and discharge range was 0-0.55V, and the discharge current density was 1Ag -1 When the specific capacitance is 900-1000F g -1 .

[0032] In order to prove the cycle stability of MCO / NiMo-LDH, the cycle stability was tested in a dual-electrode system with MCO / NiMo-LDH as the positive electrode and activated carbon AC as the negative electrode. The test results showed that the capacitance retention rate of MCO / NiMo-LDH was 70-80% when the cycle number was 5000.

[0033] Therefore, the MCO / NiMo-LDH composite material of the present invention has the following advantages over the prior art:

[0034] 1. MCO is used as the substrate of the composite material, and NiMo-LDH nanosheets are grown in situ on the surface. MCO has the characteristics of structural stability, which can prevent the collapse of NiMo-LDH, thereby maintaining the microscopic morphology of its nanosheets, that is, increasing the stability of the composite material; the synergistic effect of Ni and Mo elements, and the electronic structure changes brought about by the high oxidation state of Mo can reduce the agglomeration of LDH during the electrochemical reaction;

[0035] 2. MCO and NiMo-LDH form a core-shell structure, which can prevent volume changes during the cycle. At the same time, in the core-shell structure, NiMo-LDH nanosheets as shell structures can protect MCO as the core structure from electrolyte corrosion and side reactions, thereby reducing structural damage and volume changes, and ultimately improving cycle stability;

[0036] 3. In the core-shell structure, there is a synergistic effect between MCO and LDH nanosheets, which can promote the flow of electrons from the shell structure to the core structure, that is, accelerate the transfer of electrons and increase the rate of electrochemical reactions, thereby increasing the specific capacitance of the composite material;

[0037] 4. Interconnected nanosheets are beneficial for shortening the distance of electron diffusion, and can increase the contact surface with the electrolyte, provide more active sites, improve reaction kinetics, and generate more pseudocapacitance;

[0038] Therefore, compared with the prior art, the present invention solves the problem of volume change of the material during the cycle and provides more reactive sites, that is, while improving the specific capacitance of the composite material, the stability of the material is maintained. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 XRD patterns of MCO obtained in step 1 of Example 1, MCO / NiMo-LDH obtained in step 2 of Example 1, and NiMo-LDH obtained in comparative example 1;

[0040] Figure 2 This is a SEM image of the MCO obtained in step 1 of Example 1;

[0041] Figure 3 The charge and discharge curves of MCO obtained in step 1 of Example 1 and MCO / NiMo-LDH obtained in step 2 of Example 1;

[0042] Figure 4 This is a SEM image of MCO / NiMo-LDH obtained in step 2 of Example 1;

[0043] Figure 5 TEM image of MCO / NiMo-LDH obtained in step 2 of Example 1;

[0044] Figure 6 The charge and discharge curve of MCO / NiMo-LDH obtained in step 2 of Example 1;

[0045] Figure 7 The cycle life curve of MCO / NiMo-LDH obtained in step 2 of Example 1;

[0046] Figure 8 This is the SEM image of NiMo-LDH obtained in Comparative Example 1;

[0047] Fig. 9 The charge-discharge curves of MCO / NiMo-LDH obtained in step 2 of Example 1 and NiMo-LDH obtained in Comparative Example 1;

[0048] Fig.10 This is the SEM image of MCO / NiMo-LDH-0.5 obtained in Comparative Example 2;

[0049] Fig.11 The charge-discharge curves of MCO / NiMo-LDH obtained in step 2 of Example 1, MCO / NiMo-LDH-0.5 obtained in Comparative Example 2, and MCO / NiMo-LDH-2 obtained in Comparative Example 3;

[0050] Fig.12 This is the SEM image of MCO / NiMo-LDH-2 obtained in Comparative Example 3. DETAILED DESCRIPTION

[0051] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0052] Example 1

[0053] A method for preparing spherical manganese cobalt oxide loaded nickel-molybdenum nanosheets MnCo2O4 / NiMo-LDH comprises the following steps:

[0054] Step 1, preparation of spherical manganese cobaltate MnCo2O4, first, with a stirring time of 30 minutes, 0.5mmol manganese nitrate tetrahydrate and 1mmol cobalt nitrate hexahydrate are placed in 40mL isopropanol and stirred to obtain solution A, then, with a stirring time of 30 minutes, 8mL glycerol is placed in solution A and continued to stir to obtain solution B, then, under the conditions of a hydrothermal temperature of 140°C and a hydrothermal time of 6h, solution B is subjected to a hydrothermal reaction, finally, the reaction product is washed with anhydrous ethanol, and then vacuum dried under the conditions of a drying temperature of 60°C and a drying time of 12h to obtain a Mn-Co-gly precursor, finally, the Mn-Co-gly precursor is calcined at a calcination temperature of 450°C and a calcination time of 2h to obtain spherical manganese cobaltate MnCo2O4, referred to as MCO;

[0055] In order to prove the composition of MCO, XRD test was carried out. The test results are as follows Figure 1 As shown, MCO has the characteristic peak of MnCo2O4. The test results show that step 1 successfully synthesized MnCo2O4.

[0056] In order to verify the microstructure of MCO, SEM test was performed. The test results are shown in Figure 2 As shown, the microstructure of MCO is a spherical structure with a size of 1.3-1.4 μm.

[0057] In order to prove the electrochemical performance of MCO, electrochemical performance tests were carried out. The test results are shown in Figure 3 As shown, the charge and discharge are in the range of 0-0.55V, and the discharge current density is 1Ag -1 When the specific capacitance of MCO is 110.7 F g -1 .

[0058] Step 2, preparation of MCO / NiMo-LDH. First, 1 mmol nickel nitrate dihydrate, 1 mmol sodium molybdate dihydrate, and 5 mmol urea are placed in 50 mL deionized water and stirred for 30 min to obtain solution D. Then, 0.08 g of MCO obtained in step 1 is placed in solution D to obtain solution E. Then, solution E is subjected to a hydrothermal reaction at a hydrothermal temperature of 120° C. and a hydrothermal reaction time of 5 h. Finally, the reaction product is washed with deionized water and anhydrous ethanol in turn, and then vacuum dried at a drying temperature of 60° C. and a drying time of 12 h to obtain spherical manganese cobalt oxide-loaded nickel-molybdenum nanosheets MnCo2O4 / NiMo-LDH, referred to as MCO / NiMo-LDH.

[0059] In order to prove the composition of MCO / NiMo-LDH, XRD test was carried out. The test results are shown in Figure 1As shown, MCO / NiMo-LDH has characteristic peaks of NiMo-LDH in addition to the characteristic peaks of MnCo2O4. Compared with step 1, it can be seen that step 2 successfully synthesized NiMo-LDH.

[0060] In order to verify the microstructure of MCO / NiMo-LDH, SEM test was performed. The test results are shown in Figure 4 As shown, the microstructure of MCO / NiMo-LDH is a spherical structure with a size of 1.4-1.5 μm, and is evenly coated with a nanosheet structure. Combined with the XRD test results, it can be seen that the nanosheet structure is NiMo-LDH.

[0061] In order to further verify the microstructure of MCO / NiMo-LDH, TEM test was carried out. The test results are shown in Figure 5 As shown, the microstructure of MCO / NiMo-LDH is a core-shell structure. Combined with the XRD test results, it can be seen that MCO is a core structure and NiMo-LDH is a shell structure.

[0062] In order to prove the electrochemical performance of MCO / NiMo-LDH, electrochemical performance tests were carried out. The test results are shown in Figure 6 As shown, the charge and discharge are in the range of 0-0.55V, and the discharge current density is 1Ag -1 When the specific capacitance is 1003F g -1 .

[0063] In order to prove the cycling stability of MCO / NiMo-LDH, the cycling stability was tested in a dual-electrode system with MCO / NiMo-LDH as the positive electrode and activated carbon AC as the negative electrode. Figure 7 As shown, when the cycle number is 5000, the capacitance retention rate of MCO / NiMo-LDH is 71% and the Coulombic efficiency is 100%.

[0064] In order to demonstrate the role of MnCo2O4 in the composite material, Comparative Example 1 is provided, in which NiMo-LDH is prepared without adding MnCo2O4.

[0065] Comparative Example 1

[0066] A method for preparing NiMo-LDH without adding MnCo2O4, wherein the steps not specifically described are the same as those in Example 1, except that: step 1 is not required, and in step 2, MCO is not added, and the obtained material is named NiMo-LDH.

[0067] In order to prove the composition of NiMo-LDH, XRD test was carried out. The test results are shown in Figure 1As shown, NiMo-LDH only has the characteristic peaks of NiMo-LDH. The test results show that not adding MnCo2O4 does not affect the preparation of NiMo-LDH.

[0068] In order to verify the microstructure of NiMo-LDH, SEM test was performed. The test results are shown in Figure 8 As shown, the microstructure is an irregular nanosheet structure with a size of 1-2 μm. Compared with Example 1, it can be seen that adding MnCo2O4 can adjust the microstructure.

[0069] In order to prove the electrochemical performance of NiMo-LDH, electrochemical performance tests were carried out. The test results are shown in Fig. 9 As shown, when charging and discharging in the voltage range of 0-0.55 V and the current density is 1Ag-1, the specific capacitance is 829F g-1. Compared with Example 1, it can be seen that adding MnCo2O4 can improve the specific capacitance performance by 21%.

[0070] It can be seen from Example 1 and Comparative Example 1 that the role of MCO is to act as a carrier to adjust the micromorphology of the composite material, on the one hand, to prevent the agglomeration of NiMo-LDH nanosheets and improve the stability of the composite material, and on the other hand, to increase the contact area between the composite material and the electrolyte.

[0071] In order to demonstrate the effect of the ratio of Ni to Mo on the performance, Comparative Examples 2 and 3 are provided, in which the molar ratio of Ni to Mo, referred to as MCO / NiMo-LDH, is prepared with a Ni / Mo ratio of 1:2 and 2:1, respectively.

[0072] Comparative Example 2

[0073] A method for preparing MCO / NiMo-LDH with a Ni / Mo ratio of 1:2, wherein the steps not specifically described are the same as those in Example 1, except that in step 2, the amount of sodium molybdate dihydrate added is changed from 1 mmol to 2 mmol, and the obtained composite material is named MCO / NiMo-LDH-0.5.

[0074] In order to verify the microstructure of MCO / NiMo-LDH-0.5, SEM test was performed. The test results are shown in Fig.10 As shown, the basic microstructure of MCO / NiMo-LDH-0.5 is still a spherical structure with a size of 1.3-1.5 μm. However, there are almost no nanosheets loaded on the surface of the spherical structure, and there are messy nanosheets around MCO, that is, the nanosheets grow alone and are not successfully loaded to form a core-shell structure with MCO.

[0075] Compared with Example 1, it can be seen that when the amount of Mo element added increases, NiMo-LDH nanosheets can also be formed, but they cannot be loaded on the MCO surface. The reason is that the in situ growth of NiMo-LDH nanosheets on the MCO surface requires lattice matching of the two components, and due to the excessive addition of Mo element, the formed NiMo-LDH produces lattice distortion, which leads to the inability of NiMo-LDH nanosheets to form on the MCO surface. The direct consequence is that the core-shell structure cannot be formed, and the synergistic effect brought by the core-shell structure cannot be obtained, thereby significantly reducing the specific capacitance.

[0076] In order to prove the electrochemical performance of MCO / NiMo-LDH-0.5, electrochemical performance tests were carried out. The test results are shown in Fig.11 As shown, the charge and discharge voltage range is 0-0.55V, and the current density is 1Ag -1 When the specific capacitance is 729F g -1 Compared with Example 1, the Ni / Mo ratio is 1:2, that is, when the amount of Mo added is increased, the specific capacitance is reduced by 27%. The test results confirm the above conclusion, that is, when the amount of Mo added is excessive, the specific capacitance is significantly reduced.

[0077] Comparative Example 3

[0078] A method for preparing MCO / NiMo-LDH with a Ni / Mo ratio of 2:1, wherein the steps not specifically described are the same as those in Example 1, except that in step 2, the amount of nickel nitrate hexahydrate added is changed from 1 mmol to 2 mmol, and the obtained composite material is named MCO / NiMo-LDH-2.

[0079] In order to verify the microstructure of MCO / NiMo-LDH-2, SEM test was performed. The test results are shown in Fig.12 As shown in the figure, the basic microstructure of MCO / NiMo-LDH-2 is still a spherical structure with a size of 1.3-1.5μm. However, only a small amount of nanosheets are sparsely loaded on the surface of the spherical structure. The reason is that the nanosheets grow slowly, so that although the nanosheets can be successfully loaded on the surface of MCO, they cannot form a complete core-shell structure.

[0080] Compared with Example 1, it can be seen that when the amount of Ni element added increases, NiMo-LDH nanosheets can grow in situ on the MCO surface, but the nanosheet structure is sparse, that is, an interconnected conductive network cannot be formed. The reason is that too much Ni element leads to stress accumulation during the nucleation process of in situ formation of NiMo-LDH nanosheets, which leads to slow growth of the nanosheets. The direct consequence is that the NiMo-LDH nanosheets, as a shell structure, cannot obtain a stable structure, nor can they protect MCO from erosion by the electrolyte and the influence of side reactions, thereby significantly reducing the specific capacitance.

[0081] In order to prove the electrochemical performance of MCO / NiMo-LDH-2, electrochemical performance tests were carried out. The test results are shown in Fig.11 As shown, the charge and discharge voltage range is 0-0.55V, and the current density is 1Ag -1 When the specific capacitance is 926F g -1 Compared with Example 1, when the Ni / Mo ratio is 2:1, that is, when the amount of Ni element added is increased, the specific capacitance is reduced by 8%. The test results confirm the above conclusion, that is, when the amount of Ni element added is excessive, the specific capacitance is significantly reduced.

[0082] It can be seen from Example 1, Comparative Example 2 and Comparative Example 3 that the Ni / Mo ratio significantly affects the in-situ formation and loading of NiMo-LDH nanosheets, that is, affects the microscopic morphology, and further affects the electrochemical properties of the material.

Claims

1. A spherical manganese cobalt oxide loaded nickel molybdenum nanosheet MnCo2O4 / NiMo-LDH, characterized in that: Firstly, a spherical Mn-Co-gly precursor is prepared by a hydrothermal method, and then spherical manganese cobalt oxide MnCo2O4 is obtained by calcination. Then, MnCo2O4 is used as a carrier to load layered hydroxide NiMo-LDH by a hydrothermal method to obtain spherical manganese cobalt oxide loaded nickel-molybdenum nanosheets MnCo2O4 / NiMo-LDH, referred to as MCO / NiMo-LDH. The raw materials for preparing the Mn-Co-gly are manganese nitrate tetrahydrate, cobalt nitrate hexahydrate, isopropanol and glycerol; The raw materials for preparing the NiMo-LDH are nickel nitrate hexahydrate, sodium molybdate dihydrate and urea.

2. The spherical manganese cobalt oxide loaded nickel molybdenum nanosheets MCO / NiMo-LDH according to claim 1, characterized in that: The microscopic morphology of the MCO / NiMo-LDH is a spherical structure, the surface of which is uniformly coated with nanosheets with a size of 1.4-1.5 μm. NiMo-LDH is used as a carrier and is in-situ loaded on the surface of MCO.

3. The spherical manganese cobalt oxide loaded nickel molybdenum nanosheets MCO / NiMo-LDH according to claim 1, characterized in that: The MCO / NiMo-LDH has a core-shell structure, wherein MCO is a core structure and NiMo-LDH is a shell structure.

4. A method for preparing spherical manganese cobalt oxide loaded nickel molybdenum nanosheets MnCo2O4 / NiMo-LDH, characterized in that The following steps are involved: Step 1, preparation of manganese cobalt oxide MnCo2O4, first, under certain conditions, tetrahydrated manganese nitrate and hexahydrated cobalt nitrate are placed in isopropanol and stirred to obtain solution A, then, under certain conditions, glycerol is placed in solution A and continued to stir to obtain solution B, under certain conditions, solution B is subjected to hydrothermal reaction, then, the reaction product is washed with anhydrous ethanol, and then vacuum dried under certain conditions to obtain Mn-Co-gly precursor, and finally, under certain conditions, the Mn-Co-gly precursor is calcined to obtain spherical manganese cobalt oxide MnCo2O4, referred to as MCO; Step 2, preparation of MCO / NiMo-LDH. First, under certain conditions, nickel nitrate hexahydrate, sodium molybdate dihydrate and urea are placed in deionized water and stirred to obtain solution D. Then, the MCO obtained in step 1 is placed in solution D to obtain solution E. Then, under certain conditions, solution E is subjected to a hydrothermal reaction. Finally, the reaction product is washed with deionized water and anhydrous ethanol in turn, and then vacuum dried under certain conditions to obtain spherical manganese cobalt oxide-loaded nickel-molybdenum nanosheets MnCo2O4 / NiMo-LDH, referred to as MCO / NiMo-LDH.

5. The preparation method according to claim 4, characterized in that: In the step 1, the molar ratio of manganese nitrate tetrahydrate to cobalt nitrate hexahydrate is 1:2; In the step 2, the molar ratio of nickel nitrate hexahydrate, sodium molybdate dihydrate and urea is 1:1:5, and the mass of MCO is 0.08-0.14 g.

6. The preparation method according to claim 4, characterized in that: In step 1, the conditions for preparing solution A and solution B are that the stirring time is 30-60 min; the conditions for vacuum drying are that the drying temperature is 60-80° C. and the drying time is 12-24 h; In the step 1, the conditions for the hydrothermal reaction of solution B are: the hydrothermal temperature is 120-140° C., and the hydrothermal time is 4-6 hours; In the step 1, the calcination conditions are: in air, the calcination temperature is 350-450° C., and the calcination time is 2-3 hours.

7. The preparation method according to claim 4, characterized in that: In step 2, the conditions for preparing solution D and solution B are that the stirring time is 30-60 min; the conditions for vacuum drying are that the drying temperature is 60-80° C. and the drying time is 12-24 h; In step 2, the conditions for the hydrothermal reaction of solution E are: the hydrothermal temperature is 120-140° C., and the hydrothermal reaction time is 4-6 hours; the conditions for vacuum drying are: 60-80° C., the drying temperature is 60-80° C., and the drying time is 12-24 hours.

8. The spherical manganese cobalt oxide loaded nickel molybdenum nanosheets MCO / NiMo-LDH according to claim 1, characterized in that: When used as supercapacitor electrode material, the specific capacitance of MCO / NiMo-LDH is 900-1000 F g -1 .

9. The spherical manganese cobalt oxide loaded nickel molybdenum nanosheets MCO / NiMo-LDH according to claim 1, characterized in that: When used as a supercapacitor electrode material, MCO / NiMo-LDH is used as the positive electrode and activated carbon AC is used as the negative electrode. When the number of cycles is 5000, the capacitance retention rate is 70-80%.